High-strength wood nanocellulose membrane and preparation method thereof
By performing multi-step treatment of biomass straw, high-strength lignin-containing nanocellulose films are prepared, which solves the problems of high cost of raw materials and difficult large-scale production in the prior art, and achieves low-cost and efficient large-scale production.
Patent Information
- Application Number
- CN202411675088.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The prior art is difficult to effectively use biomass straw to prepare high-strength lignin-containing nanocellulose films, and the production cost is high and large-scale production is difficult.
The biochemical mechanical pulp of wheat grass is prepared by heating the biomass straw through alkali liquid, enzymatic decomposition, mechanical refining, etc., followed by dispersion and screening and ultra-fine particle grinding to obtain a nanocellulose dispersion containing lignin, and finally a high-strength ligno nanocellulose membrane is prepared by vacuum filtration.
It has achieved the preparation of high-strength nanocellulose membranes using biomass straw as raw materials, with low production costs, suitable for large-scale applications, and improved the strength and transparency of the membrane.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocellulose membranes, and in particular to a high-strength wood nanocellulose membrane and a preparation method thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Nanocellulose membranes have good biodegradability and renewability, and are expected to replace non-degradable plastic membranes to a certain extent. High-strength nanocellulose membranes will have a wider application space. Nanocellulose membranes are mainly made of nanocellulose by vacuum filtration, electrospinning or solution spin coating, so the performance of nanocellulose membranes is closely related to the performance of nanocellulose.
[0004] At present, the production of nanocellulose generally uses dissolving pulp and bleached chemical pulp with high delignification and high cellulose content, which has caused a waste of resources to a certain extent. The treatment process also produces a lot of waste liquid, which increases production costs and affects the ecological environment. Studies have found that nanocellulose containing lignin not only retains the characteristics of nanocellulose, but also has good dispersibility, hydrophobicity, UV resistance and thermal stability due to the presence of lignin.
[0005] At present, the raw materials of nanocellulose membranes mainly come from high-purity fibers of wood, and the raw material cost is relatively high; and the existing technology often requires the wood to be crushed, the preparation cost is relatively high, and large-scale production is more difficult. Biomass straw (such as wheat straw, rice straw, corn straw, etc.) is an agricultural byproduct with high renewability, which can achieve continuous supply and lower cost, but its cellulose content is low (usually less than 40%), which makes it more difficult to use. At the same time, the performance of the nanocellulose membrane obtained from it as a raw material will be significantly affected by the preparation conditions, and it is difficult to obtain a nanocellulose membrane with high strength.
[0006] Therefore, how to provide a method for preparing high-strength nanocellulose membrane containing lignin using biomass straw as raw material is an urgent problem to be solved. Summary of the invention
[0007] In view of this, the present invention provides a high-strength wood nanocellulose membrane and a preparation method thereof. The provided method uses biomass straw as raw material, prepares lignin-containing nanocellulose by enzyme / chemical / mechanical method, and obtains a high-strength wood nanocellulose membrane through the preparation, which has low production cost and is suitable for large-scale application.
[0008] In a first aspect, the present invention provides a method for preparing a high-strength wood nanocellulose film, comprising the following steps:
[0009] The biomass straw is subjected to a heating treatment with an alkaline solution having a concentration of 6 to 10 wt%, and after washing and neutralization, cellulase is added for enzymolysis, and after inactivation, mechanical pulping is performed to obtain wheat straw biochemical mechanical pulp; the wheat straw biochemical mechanical pulp is debonded and sieved to obtain fine fibers, and the fine fibers are subjected to ultrafine particle grinding to obtain a nanocellulose dispersion containing lignin, which is then vacuum filtered and dried.
[0010] Preferably, the alkali solution is an aqueous solution of NaOH or KOH.
[0011] Preferably, the mass ratio of the biomass straw to the alkali solution is 1:(4-8).
[0012] Preferably, the temperature of the heating treatment is 90-100° C., and the time of the heating treatment is 40-60 min.
[0013] Preferably, the dosage of the cellulase is 15-25 U / g; the solution in the enzymatic hydrolysis process is a citric acid-sodium citrate buffer solution with a pH of 4.8-5.2.
[0014] Preferably, the enzymatic hydrolysis temperature is 50-60°C, and the enzymatic hydrolysis time is 50-70 min; the inactivation temperature is 95-100°C, and the inactivation time is 8-15 min.
[0015] Preferably, before the fluffing and screening step, the step of de-latching the wheat straw biochemical mechanical pulp is also included, and the de-latching time is 50 to 80 minutes.
[0016] Preferably, the diameter of the fine fibers is below 0.15 mm.
[0017] Preferably, the concentration of the lignin-containing nanocellulose dispersion is 0.8-1.5 wt %.
[0018] In a second aspect, the present invention provides a high-strength wood nanocellulose film prepared by the above preparation method.
[0019] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0020] (1) The present invention uses biomass straw as raw material, prepares lignin-containing nanocellulose by enzyme / chemical / mechanical method, and then prepares nanocellulose membrane by vacuum filtration method. The preparation process has mild reaction conditions and low production cost. It can also realize the high-value utilization of biomass straw and is suitable for large-scale application.
[0021] (2) The nanocellulose film prepared by the present invention has good strength, the film breaking stress is above 45 MPa, and the highest can reach nearly 100 MPa, and the transparency is good (>80%), and it can be used in the fields of food packaging and has good application prospects. DETAILED DESCRIPTION
[0022] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0023] The present invention provides a method for preparing a high-strength wood nanocellulose film, comprising the following steps:
[0024] The biomass straw is subjected to a heating treatment with an alkaline solution having a concentration of 6 to 10 wt%, and after washing and neutralization, cellulase is added for enzymolysis, and after inactivation, mechanical pulping is performed to obtain wheat straw biochemical mechanical pulp; the wheat straw biochemical mechanical pulp is debonded and sieved to obtain fine fibers, and the fine fibers are subjected to ultrafine particle grinding to obtain a nanocellulose dispersion containing lignin, which is then vacuum filtered and dried.
[0025] The present invention does not impose any particular limitation on the source of the biomass straw, which can be selected from wheat straw, corn straw or rice straw. In one or more embodiments of the present invention, the biomass straw is preferably wheat straw.
[0026] The present invention further comprises the steps of dust removal and washing of the straw before the alkaline solution heating treatment step. The present invention does not impose any special restrictions on the dust removal and washing processes, and the commonly used methods in the art can be used.
[0027] In the present invention, the alkali solution is an aqueous solution of NaOH or KOH, more preferably an aqueous solution of NaOH. The present invention first uses alkali solution (to destroy the wax layer on the surface of the straw to a certain extent, and to remove a part of the lignin in the raw material). The present invention finds that the concentration of the alkali solution will affect the lignin content, particle size and other properties of the lignin-containing nanocellulose, thereby affecting the mechanical strength of the final nanocellulose film. When the alkali solution concentration is too low, the mechanical strength of the resulting nanocellulose film is low; when the alkali solution concentration increases, the degree of dissolution of lignin increases accordingly, the bonding effect of lignin on the fiber is weakened, and the corresponding film strength will also be enhanced to a certain extent. However, too high an alkali solution concentration does not significantly improve the mechanical properties, and will also result in too low a lignin content, which will result in a decrease in the hydrophobicity, UV resistance and thermal stability of the resulting nanocellulose film.
[0028] In the present invention, the mass ratio of the biomass straw to the alkali solution is 1:(4-8), more preferably 1:(4-6). Excessive use of alkali solution will not improve the effect, but will increase the difficulty of waste liquid treatment.
[0029] In the present invention, the temperature of the heating treatment is 90-100° C., and the time of the heating treatment is 40-60 minutes.
[0030] In the present invention, the dosage of the cellulase is 15-25 U / g; the solution in the enzymatic hydrolysis process is a citric acid-sodium citrate buffer solution with a pH of 4.8-5.2. After being treated with cellulase, the cellulose becomes softer and easier to fiberize.
[0031] In the present invention, the temperature of the enzymolysis is 50-60° C., and the time of the enzymolysis is 50-70 min; the temperature of the inactivation is 95-100° C., and the time of the inactivation is 8-15 min.
[0032] The present invention does not impose any special restrictions on the mechanical refining process. The present invention preferably uses a high-consistency disc refiner, which includes two disc refiners with disc refiner gaps of 0.5 mm and 0.15 mm, respectively. Those skilled in the art can also adjust according to actual needs.
[0033] In the present invention, before the fluffing and screening step, the step of removing latent fibers from the wheat straw biochemical mechanical pulp is also included, and the removal time is 50 to 80 minutes. The removal of latent fibers reduces the curvature of the fibers and increases the efficiency during screening.
[0034] In the present invention, the diameter of the fine fibers is less than 0.15 mm. The present invention does not impose any special restrictions on the process and equipment of the debonding and screening. The fine fibers obtained by debonding and screening can ensure the uniformity of microfibrillation during subsequent ultrafine particle grinding, while reducing energy consumption and increasing the yield of lignin-containing nanocellulose.
[0035] The present invention does not impose any special restrictions on the specific steps of ultrafine particle grinding. The present invention preferably uses an ultrafine particle grinder to perform microfibrillation treatment, with a concentration of 0.8 to 1.5 wt%, and the adjustment gaps are +2, 0, -2, -5, and -8, respectively. The number of cycles in each stage is 8 to 10 times, and finally a nanocellulose dispersion containing lignin is obtained, and the concentration of the nanocellulose dispersion containing lignin is 0.8 to 1.5 wt%.
[0036] The present invention also provides a high-strength wood nanocellulose film prepared by the above preparation method. The film has a breaking stress of more than 30 MPa, up to nearly 100 MPa, and a transparency of more than 80%. It can be used in the fields of food packaging and has good application prospects.
[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0038] Example 1
[0039] This embodiment provides a method for preparing a high-strength wood nanocellulose film.
[0040] (1) Weigh 500 g of absolutely dry wheat straw, remove dust, wash, and measure the moisture content;
[0041] (2) The wheat straw in step (1) was subjected to alkali pretreatment (6 wt% NaOH aqueous solution) with a solid-liquid ratio of 1:5; the treatment temperature was 95° C., the treatment time was 50 min, and the straw was fully rubbed during the treatment. After the treatment, it was washed to neutrality and placed in a sealed bag for moisture balance for 8 h, and the moisture content was measured;
[0042] (3) treating the wheat straw obtained in step (2) with cellulase at an enzyme dosage of 20 U / g, treating in a water bath for 60 min, treating at a temperature of 55° C., using a citric acid-sodium citrate buffer solution with a pH of 5; kneading the straw thoroughly during the treatment, and inactivating the straw in 100° C. water for 10 min after the treatment;
[0043] (4) mechanically treating the wheat straw in step (3) by using a high-consistency disc refiner for continuous refining at both ends, with the gaps between the two stages being 0.5 mm and 0.15 mm respectively, and drying the obtained wheat straw biochemical mechanical pulp;
[0044] (5) putting the wheat straw biochemical mechanical pulp in step (4) into a sealed bag, adding a certain amount of water, and placing the whole in a constant temperature water bath at 60° C. to de-latten for 60 minutes;
[0045] (6) The wheat straw biochemical mechanical pulp in step (5) is dispersed and screened by a flat screen, wherein the screen gap of the flat screen is 0.15 mm, to obtain fine fibers with a diameter of less than 0.15 mm;
[0046] (7) The fine fibers in step (6) are subjected to microfibrillation treatment by an ultrafine grinding machine, with a feed concentration of 1 wt%. The gaps are adjusted to +2, 0, -2, -5, and -8, respectively, and the number of cycles for each stage is 10, and finally a nanocellulose dispersion containing lignin is obtained;
[0047] (8) The lignin-containing nanocellulose dispersion obtained in step (7) is vacuum filtered to obtain a nanocellulose membrane. The quantitative weight of the nanocellulose membrane is 60 g / m 2 , compact the wet film with heavy objects and dry it in an oven at 50℃ for 24h.
[0048] The average length of the wheat straw biochemical mechanical pulp fiber obtained in this example is 0.809±0.008mm, the average fiber width is 27.1±0.2μm; the lignin content in the obtained nanocellulose is 17.85wt%, the average particle size of the nanocellulose is 3.98±0.97nm, and the crystallinity is 64.78%. The transparency of the obtained nanocellulose film is 83.00%, the maximum stress when the film breaks is 48.19MPa, and the temperature at the maximum pyrolysis rate is 345.14℃.
[0049] Example 2
[0050] This embodiment provides a method for preparing a high-strength wood nanocellulose film.
[0051] (1) Weigh 500 g of absolutely dry wheat straw, remove dust, wash, and measure the moisture content;
[0052] (2) The wheat straw in step (1) was subjected to alkali pretreatment (8 wt % NaOH aqueous solution) with a solid-liquid ratio of 1:5; the treatment temperature was 95° C., the treatment time was 50 min, and the straw was fully rubbed during the treatment. After the treatment, it was washed to neutrality and placed in a sealed bag for moisture balance for 8 h, and the moisture content was measured;
[0053] (3) treating the wheat straw obtained in step (2) with cellulase at an enzyme dosage of 20 U / g, treating in a water bath for 60 min, treating at a temperature of 55° C., using a citric acid-sodium citrate buffer solution with a pH of 5; kneading the straw thoroughly during the treatment, and inactivating the straw in 100° C. water for 10 min after the treatment;
[0054] (4) mechanically treating the wheat straw in step (3) by using a high-consistency disc refiner for continuous refining at both ends, with the gaps between the two stages being 0.5 mm and 0.15 mm respectively, and drying the obtained wheat straw biochemical mechanical pulp;
[0055] (5) putting the wheat straw biochemical mechanical pulp in step (4) into a sealed bag, adding a certain amount of water, and placing the whole in a constant temperature water bath at 60° C. to de-latten for 60 minutes;
[0056] (6) The wheat straw biochemical mechanical pulp in step (5) is dispersed and screened by a flat screen, wherein the screen gap of the flat screen is 0.15 mm, to obtain fine fibers with a diameter of less than 0.15 mm;
[0057] (7) The fine fibers in step (6) are subjected to microfibrillation treatment by an ultrafine grinding machine, with a feed concentration of 1 wt %, an adjustment gap of +2, 0, -2, -5, and -8, respectively, and each stage is cycled 10 times to finally obtain a nanocellulose dispersion containing lignin;
[0058] (8) The lignin-containing nanocellulose dispersion obtained in step (7) is vacuum filtered to obtain a nanocellulose membrane. The quantitative weight of the nanocellulose membrane is 60 g / m 2 , compact the wet film with heavy objects and dry it in an oven at 50℃ for 24h.
[0059] The average length of the wheat straw biochemical mechanical pulp fiber obtained in this example is 0.883±0.021mm, the average fiber width is 25.7±0.1μm; the lignin content in the obtained nanocellulose is 15.76wt%, the average particle size of the nanocellulose is 3.88±0.86nm, and the crystallinity is 66.30%. The transparency of the obtained nanocellulose film is 89.03%, the maximum stress when the film breaks is 93.99MPa, and the temperature at the maximum pyrolysis rate is 344.6℃.
[0060] Example 3
[0061] The difference between this embodiment and embodiment 1 is that the alkaline pretreatment in step (2) of this embodiment adopts a 10 wt % NaOH aqueous solution.
[0062] The average length of the wheat straw biochemical mechanical pulp fiber obtained in this example is 0.901±0.015mm, the average fiber width is 23.2±0.3μm, the lignin content in the obtained nanocellulose is 13.07wt%, the average particle size of the nanocellulose is 3.63±0.7nm, and the crystallinity is 67.25%. The transparency of the obtained nanocellulose film is 91.21%, the maximum stress when the film breaks is 99.66MPa, and the temperature at the maximum pyrolysis rate is 329.16℃.
[0063] Comparative Example 1
[0064] The difference between this comparative example and Example 1 is that the alkaline pretreatment in step (2) of this comparative example adopts 2 wt % NaOH aqueous solution.
[0065] The average length of the wheat straw biochemical mechanical pulp fiber obtained in this comparative example is 0.699±0.011mm, and the average fiber width is 29.9±0.1μm; the lignin content in the obtained nanocellulose is 21.70wt%, the average particle size of the nanocellulose is 4.30±1.03nm, and the crystallinity is 56.92%. The transparency of the obtained nanocellulose film is 15.8%, the maximum stress when the film breaks is 26.56MPa, and the temperature at the maximum pyrolysis rate is 350.65℃.
[0066] Comparative Example 2
[0067] The difference between this comparative example and Example 1 is that the alkaline pretreatment in step (2) of this comparative example adopts 4 wt % NaOH aqueous solution.
[0068] The average length of the wheat straw biochemical mechanical pulp fiber obtained in this comparative example is 0.758±0.015mm, the average fiber width is 30.1±0.2μm, the lignin content in the obtained nanocellulose is 19.17wt%, the average particle size of the nanocellulose is 3.22±0.8nm, and the crystallinity is 59.25%. The transparency of the obtained nanocellulose film is 21.02%, the maximum stress when the film breaks is 29.30MPa, the temperature at the maximum pyrolysis rate is 348.86℃, and the obtained nanocellulose.
[0069] Comparative Example 3
[0070] The difference between this comparative example and Example 1 is that the cellulase treatment step (3) is not performed in this comparative example. The specific steps are as follows:
[0071] (1) Weigh 500 g of absolutely dry wheat straw, remove dust, wash, and measure the moisture content;
[0072] (2) The wheat straw in step (1) was subjected to alkali pretreatment (6 wt% NaOH aqueous solution) with a solid-liquid ratio of 1:5; the treatment temperature was 95° C., the treatment time was 50 min, and the straw was fully rubbed during the treatment. After the treatment, it was washed to neutrality and placed in a sealed bag for moisture balance for 8 h, and the moisture content was measured;
[0073] (3) mechanically treating the wheat straw in step (3) by using a high-consistency disc refiner for continuous refining at both ends, with the gaps between the two stages being 0.5 mm and 0.15 mm respectively, and drying the obtained wheat straw biochemical mechanical pulp;
[0074] (4) putting the wheat straw biochemical mechanical pulp in step (4) into a sealed bag, adding a certain amount of water, and placing the whole in a constant temperature water bath at 60° C. to de-latten for 60 minutes;
[0075] (5) microfibrillating the wheat straw biochemical mechanical pulp in step (5) by an ultrafine grinding machine, with a feed concentration of 1 wt %, adjusting the gaps to +2, 0, -2, -5, and -8, respectively, and performing 10 cycles in each stage, to finally obtain a nanocellulose dispersion containing lignin;
[0076] (6) The lignin-containing nanocellulose dispersion obtained in step (6) is vacuum filtered to obtain a nanocellulose membrane. The quantitative weight of the nanocellulose membrane is 60 g / m 2 , compact the wet film with heavy objects and dry it in an oven at 50℃ for 24h.
[0077] The average length of the wheat straw biochemical mechanical pulp fiber obtained in this comparative example is 0.810±0.004mm, the average fiber width is 29.1±0.1μm, the lignin content in the obtained nanocellulose is 17.05wt%, the average particle size of the nanocellulose is 4.03±0.9nm, and the crystallinity is 62.52%. The transparency of the obtained nanocellulose film is 81.50%, the maximum stress when the film breaks is 39.20MPa, and the temperature at the maximum pyrolysis rate is 345.15℃.
[0078] Comparative Example 4
[0079] The difference between this comparative example and Example 1 is that the delamination and screening step (6) is not performed in this comparative example. The specific steps are as follows:
[0080] (1) Weigh 500 g of absolutely dry wheat straw, remove dust, wash, and measure the moisture content;
[0081] (2) The wheat straw in step (1) was subjected to alkali pretreatment (6 wt% NaOH aqueous solution) with a solid-liquid ratio of 1:5; the treatment temperature was 95° C., the treatment time was 50 min, and the straw was fully rubbed during the treatment. After the treatment, it was washed to neutrality and placed in a sealed bag for moisture balance for 8 h, and the moisture content was measured;
[0082] (3) treating the wheat straw obtained in step (2) with cellulase at an enzyme dosage of 20 U / g, treating in a water bath for 60 min, treating at a temperature of 55° C., using a citric acid-sodium citrate buffer solution with a pH of 5; kneading the straw thoroughly during the treatment, and inactivating the straw in 100° C. water for 10 min after the treatment;
[0083] (4) mechanically treating the wheat straw in step (3) by using a high-consistency disc refiner for continuous refining at both ends, with the gaps between the two stages being 0.5 mm and 0.15 mm respectively, and drying the obtained wheat straw biochemical mechanical pulp;
[0084] (5) putting the wheat straw biochemical mechanical pulp in step (4) into a sealed bag, adding a certain amount of water, and placing the whole in a constant temperature water bath at 60° C. to de-latten for 60 minutes;
[0085] (6) microfibrillating the wheat straw biochemical mechanical pulp in step (5) by an ultrafine grinding machine, with a feed concentration of 1 wt %, adjusting the gaps to +2, 0, -2, -5, and -8, respectively, and performing 10 cycles in each stage, to finally obtain a nanocellulose dispersion containing lignin;
[0086] (7) The lignin-containing nanocellulose dispersion obtained in step (6) is vacuum filtered to obtain a nanocellulose membrane. The quantitative weight of the nanocellulose membrane is 60 g / m 2, compact the wet film with heavy objects and dry it in an oven at 50℃ for 24h.
[0087] The average length of the wheat straw biochemical mechanical pulp fiber obtained in this comparative example is 0.776±0.004mm, the average fiber width is 23.7±0.1μm, the lignin content in the obtained nanocellulose is 17.65wt%, the average particle size of the nanocellulose is 4.12±1.89nm, and the crystallinity is 63.72%. The transparency of the obtained nanocellulose film is 82.89%, the maximum stress when the film breaks is 36.22MPa, and the temperature at the maximum pyrolysis rate is 346.30℃.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength wood nanocellulose film, characterized in that: The steps include: The biomass straw is subjected to a heating treatment with an alkaline solution having a concentration of 6 to 10 wt%, and after washing and neutralization, cellulase is added for enzymolysis, and after inactivation, mechanical pulping is performed to obtain wheat straw biochemical mechanical pulp; the wheat straw biochemical mechanical pulp is debonded and sieved to obtain fine fibers, and the fine fibers are subjected to ultrafine particle grinding to obtain a nanocellulose dispersion containing lignin, which is then vacuum filtered and dried.
2. The preparation method according to claim 1, characterized in that The alkali solution is an aqueous solution of NaOH or KOH.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the biomass straw to the alkali solution is 1:(4-8).
4. The preparation method according to claim 1, characterized in that: The temperature of the heating treatment is 90-100° C., and the time of the heating treatment is 40-60 minutes.
5. The preparation method according to claim 1, characterized in that: The dosage of the cellulase is 15-25 U / g; the solution in the enzymolysis process is a citric acid-sodium citrate buffer solution with a pH of 4.8-5.
2.
6. The preparation method according to claim 1, characterized in that: The temperature of the enzymolysis is 50-60° C., and the time of the enzymolysis is 50-70 minutes; the temperature of the inactivation is 95-100° C., and the time of the inactivation is 8-15 minutes.
7. The preparation method according to claim 1, characterized in that: The step of de-lamination of the wheat straw biochemical mechanical pulp is included before the de-lamination and screening step, and the de-lamination time is 50 to 80 minutes.
8. The preparation method according to claim 1, characterized in that: The diameter of the fine fibers is less than 0.15 mm.
9. The preparation method according to claim 1, characterized in that: The concentration of the lignin-containing nanocellulose dispersion is 0.8-1.5 wt %.
10. A high-strength wood nanocellulose film prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of nano cellulose
CN106480129A
Method for preparing hydrophobic and highly-breathable fiber film by mechanical technology
CN110452402A
Preparation of cellulose fibers
US20220081833A1
Cited By
Multi-level micro-nano fiber containing active lignin as well as preparation method and application of multi-level micro-nano fiber
CN122520943A